Load intensity in volleyball game like drills - Lehnert, M.; Stejskal, P.; Hap, P.; Vavak, M. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2008)
The key problem of training in sports games is rightfully considered the relation between match performance and training load (Argaj, 2005; Bloomfield, Fricker, & Fitch, 1992; Dobrý & Semiginovský, 1988; Laurencík, 2006; Reilly & Bangsbo, 1998; Tomajko, 2000). The training process in volleyball must result from the typical demands of match load, the specificities of players` specializations and their roles in the game system of a team, athletes` individual specificities and, at the same time, respect the trends of modern volleyball and the training process. Changing an intensive movement activity focused on performing specific tasks for particular game specializations during a relay lasting only a few seconds with relatively long time outs is regarded as a significant volleyball match load parameter (Aartrijk, 2000; Alberda, 1995; Baacke, 1994; Papageorgiou, 1999; Papegeorgiou & Timmer, 1990; Polglaze & Davson, 1992; Pridal & Zapletalová, 2003; Ureña, 2000; Zhang, 2000; Zimmermann, 1999).